Major Acetabular Defects Treated with the Burch-Schneider Antiprotrusion Cage and Impaction Bone Allograft in a Large Series: A 5- to 7- Year Follow-up Study. Issue 6 (10th November 2016) - Marx, Axel; Beier, Alexander; Richter, Anne; Lohmann, Christoph H.; Halder, Andreas M.
Introduction: Major bone defects are the greatest challenge in hip revision arthroplasty. Methods: In a prospective, consecutive nonrandomised study we followed up 74 patients with Type III (AAOS) acetabular bone defects who underwent revision hip arthroplasty with bone grafting and implantation of a Burch-Schneider anti-protrusion cage (APC). The patients were examined pre- and postoperatively according to a standardised clinical and radiological protocol. No patient was lost to follow-up. Results: 9 patients died before follow-up. In 9 other patients the APC was revised within the follow-up period. In 4 of these patients the revision was necessary because of aseptic loosening. In the remaining 5 cases joint infection, recurrent dislocation and 1 trauma were the reasons for revision. 56 patients were included in the statistical analysis. In the follow-up group the mean Harris Hip Score increased from 39.9 preoperatively to 73.2. 85% of the patients assessed their operation result as good or excellent. Conclusions: In a large consecutive series the Burch-Schneider anti-protrusion cage proved to be a valuable option in the treatment of major acetabular bone defects in hip revision surgery.